CD28 is superior to 4-1BB costimulation in generating CAR-NK cells for tumor immunotherapy - Pengchao Zhang; Xuejia Feng; Xiangyun Niu; Zhongming Liu; Minghui Li; Maoxuan Liu; Dehong Yan; Guizhong Zhang; Xiaochun Wan (Experimental Hematology & Oncology)
Abstract Chimeric antigen receptor (CAR)-NK therapy holds great potential for tumor treatment, but current CAR designs are primarily optimized for T cells, raising concerns about their suitability for NK cells. This study compared two dominant CAR designs used in T cells—CD28-CD3ζ (28z) and 4-1BB-CD3ζ (BBz)—and found that CD28 costimulation offers superior functionality in NK cells. 28z CAR-NK cells exhibited significantly better activation, cytotoxicity, and in vivo anti-tumor efficacy than BBz CAR-NK cells, with similar persistence and tumor infiltration. 28z CAR more effectively recruited the ZAP70 kinase and upregulated multiple key factors involved in immune activation, potentially augmenting CAR-NK cell function. MAP3K8, a kinase involved in inflammation and the MAPK signaling pathway, was identified as a critical mediator in enhancing 28z CAR-NK cell function. Silencing or inhibiting MAP3K8 impaired the anti-tumor activity of 28z CAR-NK cells, while its overexpression substantially improved the function of BBz CAR-NK cells. These findings provide new insights into how CD28 costimulation boosts CAR-NK cell efficacy, supporting its use into NK cell-specific CARs for cancer immunotherapy, and highlight MAP3K8 as a potential target for optimizing BBz CAR-NK cell therapy.